The good farmer - Burton, Rob, author.
1 online resource
Keywords: "Developed by the leading authors in the field, this book provides a cohesive and definitive theorisation of the concept of the 'good farmer', addressing the blind spots that have sprung up in agri-food literature as well as providing a springboard for future research. The concept of the good farmer has emerged in recent years as part of a move away from attitude and economics based understandings of farm decision-making towards a deeper understanding of culture and symbolism in agriculture. The Good Farmer shows why agricultural production is socially and culturally, as well as economically, important. It explores the history of the concept and its position in contemporary theory, as well as its use and meaning in a variety of different contexts, including landscape, environment, gender, society, and as a tool for resistance. By exploring the iÞa of the good farmer, it reveals the often-unforeseen assumptions implicit in food and agricultural policy that draw on culture, identity, and presumed notions of what is good. Finally, the book looks at the potential of the good farmer concept for addressing future, emerging issues in agriculture. This book will be of interest to students and scholars of food and agriculture and rural development, as well and professionals and policymakers involved in the food and agricultural industry"--